Study on antimicrobial effect of disinfecting solutions on alginate impression materials - Ahsan, Mohamad Rafiul; Islam, Kazi Ziaul; Begum, Jebunnesa (Update Dental College Journal, 2014)
Oral cavity contains 600 species of microbes named oral flora.Dental impressions get contaminated with micro-organisms from patients blood or saliva. So, impressions are recommended to disinfect before their further working steps. A study was carried out to find out a more effective disinfectant solution between 1% sodium hypochlorite and 2% glutaraldehyde solution on irreversible hydrocolloid impression and thereby identify their efficacy against microbial transmission to the resultant dental cast. In this study, hydrcolloid impression material was selected as the experimental elements because these are the materials which are mostly used in our country. These are disinfecting solution which are worldwide used. The findings suggested that the transmission rate from impression to the casts was 7% in control group (P<0.001). It was reduced to (0.6%) when disinfected by 1% sodium hypochlorite solution whereas transmission rate was minimum (0.08%) when disinfected by 2% glutaraldehde solution. The most important things is that it will be very easy for the clinician to produce this solution and disinfect the impression by these solutions and there will have no effect on the dimension of the impression or the cast DOI: http://dx.doi.org/10.3329/updcj.v3i1.17980 Update Dent. Coll. j: 2013; 3 (1): 18-23